A global perspective on compositions, risks, and ecological genesis of antibiotic resistance genes in biofilters of drinking water treatment plants. (15th April 2023) - Liang, Jinsong; Lin, Huan; Singh, Brajesh; Wang, Aijie; Yan, Zhenzhen
Highlights: ARGs in surface water biofilters were approximately five times higher than that of groundwater biofilters. Up to 99.61% of the ARGs on average in biofilters belong to the least and unassessed risk ranks. Only 0.23% of the ARGs on average in biofilters belong to the highest risk rank. Monobactam biosynthesis pathway is related to ARGs ecological genesis in surface water biofilters. Prodigiosin biosynthesis pathway is related to ARGs ecological genesis in groundwater biofilters. Abstract: Antibiotic resistance genes (ARGs) in biofilters of drinking water treatment plants (DWTPs) are regarded to be a remarkable potential health risk to human. A global survey on ARGs in biofilters may help evaluate their risk features as a whole. This study aims to explore the compositions, risks, and ecological genesis of ARGs in the biofilters of DWTPs. In total, 98 metagenomes of DWTP biofilters were collected from Sequence Read Archive (SRA) of National center for Biotechnology Information (NCBI), and the main ARG types were recognized, with multidrug, bacitracin, and beta-lactam as the first three types. Source water types (surface water vs. groundwater) were found to significantly influence antibiotic resistome, overpassing biofilter media and locations. Although ARG abundances of surface water biofilters were approximately five times higher than that of groundwater biofilters, the risk pattern of ARGs was highly similar between surface water biofilters and groundwater biofilters, and up to 99.61% of the ARGs on average belong to the least risk and unassessed ranks, and only 0.23% the highest risk rank. Monobactam biosynthesis pathway and prodigiosin biosynthesis pathway, two antibiotics biosynthesis pathways, were observed to be positively correlated with several ARG types and total ARG abundance in samples of surface water and groundwater biofilters, respectively, suggesting their potential roles in ecological genesis of ARGs. Overall, the results of this study would deepen our understanding of the ARG risks in biofilters of DWTPs and shed light on their ecological genesis inside. Graphical abstract: Image, graphical abstract